Exogenous selection rather than cytonuclear incompatibilities shapes asymmetrical fitness of reciprocal Arabidopsis hybrids. Issue 8 (25th March 2015) - Muir, Graham; Ruiz‐Duarte, Paola; Hohmann, Nora; Mable, Barbara K.; Novikova, Polina; Schmickl, Roswitha; Guggisberg, Alessia; Koch, Marcus A.
Abstract: Reciprocal crosses between species often display an asymmetry in the fitness of F1 hybrids. This pattern, referred to as isolation asymmetry or Darwin's corollary to Haldane's rule, is a general feature of reproductive isolation in plants, yet factors determining its magnitude and direction remain unclear. We evaluated reciprocal species crosses between two naturally hybridizing diploid species of Arabidopsis to assess the degree of isolation asymmetry at different postmating life stages. We found that pollen from Arabidopsis arenosa will usually fertilize ovules from Arabidopsis lyrata ; the reverse receptivity being less complete. Maternal A. lyrata parents set more F1 hybrid seed, but germinate at lower frequency, reversing the asymmetry. As predicted by theory, A. lyrata (the maternal parent with lower seed viability in crosses) exhibited accelerated chloroplast evolution, indicating that cytonuclear incompatibilities may play a role in reproductive isolation. However, this direction of asymmetrical reproductive isolation is not replicated in natural suture zones, where delayed hybrid breakdown of fertility at later developmental stages, or later‐acting selection against A. arenosa maternal hybrids (unrelated to hybrid fertility, e.g., substrate adaptation) may be responsible for an excess of A. lyrata maternal hybrids. Exogenous selection rather than cytonuclear incompatibilities thus shapes the asymmetrical postmating isolation in nature. Abstract : Isolation asymmetry or Darwin's Corollary to Haldane's Rule, is a general feature of reproductive isolation in plants. We test in Arabidopsis inter‐species crosses if exogenous selection rather than cyto‐nuclear incompatibilities shapes the asymmetrical postmating isolation. Our experimental system is conceptually based on a large Arabidopsis suture and introgression zone with A. arenosa and A. lyrata in Austria.